The Effect of NPK Fertilizer on Peanut Crop Production (Arachis hypogaea L.) - Andrian Imam Rahmadi; Wahyuni, Siti Hardianti; Meiliana Friska (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2024)
The need for peanuts from year to year continues to increase in line with the increasing population, community nutrition needs, food diversification, and the increasing capacity of the feed and food industry in Indonesia. N, P, and K are important factors and must be available to plants because they function as metabolic and biochemical processes of plant cells. Nitrogen is used as a builder of nucleic acids, proteins, bioenzymes, and chlorophyll. The purpose of this study was to determine the effect of NPK fertilizer on the growth and production of peanut plants. This research was conducted from January 2023 to April 2023 at the Faculty of Agriculture, Graha Nusantara University Padangsidimpuan. The method in this research is Non Factorial Randomized Group Design (RAK) with 4 types of calcium fertilizer treatments: 0 g/polybag (C0), 3 g/polybag (C1), 5 g/polybag (C2) and 7 g/polybag (C3). The results showed that NPK fertilizer affected the number of pods, pod weight and seed weight. The calcium fertilizer treatment that gives the best results on soybean crop production is in the C2 treatment, namely a dose of 5 3 g / polybag.